Post-COVID-19 condition: systemic inflammation and low functional exercise capacity - de Castro, Gabriela Salim; Gama, Leonardo R.; Ramos, Alexandre Ferreira; Gatti da Silva, Guilherme; Teixeira, Alexandre Abilio de Souza; Cunha-Neto, Edecio; de Souza, Heraldo Possolo; Marie, Suely K.; Talib, Leda L.; Coelho, Verônica; Kalil, Jorge; de Araujo, Adriana Ladeira; et al. (Frontiers in Nutrition, 2024)
Post-COVID-19 condition (PCC) is characterised by a plethora of symptoms, with fatigue appearing as the most frequently reported. The alterations that drive both the persistent and post-acute disease newly acquired symptoms are not yet fully described. Given the lack of robust knowledge regarding the mechanisms of PCC we have examined the impact of inflammation in PCC, by evaluating serum cytokine profile and its potential involvement in inducing the different symptoms reported. Methods: In this cross-sectional study, we recruited 227 participants who were hospitalised with acute COVID-19 in 2020 and came back for a follow-up assessment 6-12 months after hospital discharge. The participants were enrolled in two symptomatic groups: Self-Reported Symptoms group (SR, n=96), who did not present major organ lesions, yet reported several debilitating symptoms such as fatigue, muscle weakness, and persistent loss of sense of smell and taste; and the Self-Reported Symptoms and decreased Pulmonary Function group (SRPF, n=54), composed by individuals with the same symptoms described by SR, plus diagnosed pulmonary lesions. A Control group (n=77), with participants with minor complaints following acute COVID-19, was also included in the study. Serum cytokine levels, symptom questionnaires, physical performance tests and general clinical data were obtained in the follow-up assessment. Results: SRPF presented lower IL-4 concentration compared with Control (q=0.0018) and with SR (q=0.030), and lower IFN-α2 serum content compared with Control (q=0.007). In addition, SRPF presented higher MIP-1β serum concentration compared with SR (q=0.029). SR presented lower CCL11 (q=0.012 and q=0.001, respectively) and MCP-1 levels (q=0.052 for both) compared with Control and SRPF. SRPF presented lower G-CSF compared to Control (q=0.014). Female participants in SR and SRPF showed lower handgrip strength in relation to Control (q=0.0623 and q=0.0015, respectively). Male participants in SR and SRPF needed more time to complete the timed up-and-go test, as compared with men in the Control group (q=0.0302 and q=0.0078, respectively). Our results indicate that different PCC symptom profiles are accompanied by distinct inflammatory markers in the circulation. Of particular concern are the lower muscle function findings, with likely long-lasting consequences for health and quality of life, found for both PCC phenotypes.